IJCM_59A: Knowledge and Practice regarding Biomedical Waste Management (BMW) among Paramedical Staff and Group IV Workers in tertiary care hospitals of Mangalore - Mitra Amartya; Gupta Namya; Upadhyay Ayushi; Singh Parul; Sharma Manav; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Planning the waste management of all waste generated in healthcare facilities is a crucial task to reduce the hazards and risks to individuals and the community. Objectives: To assess the knowledge and practices regarding bio-medical waste management among paramedical staff and Group IV workers. Methods: In this cross-sectional study, 210 paramedical staff working at hospitals affiliated with Kasturba Medical College, Mangalore were assessed regarding their knowledge and practices regarding BMW. Institutional Ethics Committee permission was obtained before the commencement of the study. Data was analysed using IBM SPSS for Windows version 25.0, Armonk, New York, 25.0. Results: Among the total participants, there were 127 nurses, 6 lab technicians and 77 Group IV workers. 98.1% of healthcare providers were aware that their hospital has a waste management plan. 87.6% of healthcare providers follow hospital policies every time while disposing of waste. 92% of healthcare providers are aware of diseases transmitted by biomedical waste. The majority of the participants preferred using all five protective measures - gloves, goggles, masks, boots, and gowns while dealing with biomedical waste. Conclusion: The majority of the paramedical staff in our study were aware of the BMW management practices.